Community Service Activities Through Distribution of 1,800 Iftar Packages in Tasikmalaya City's Coastal Area - Bilqis Damai Nuraini Megantara; Gigin Ginayaturrohmah; Santia Ningrum; Iman Hardiana; Nisa Apriliani (LPPM Universitas Muhammadiyah Tasikmalaya, 2022)
Behind the development of the city of Tasikmalaya, there are still several coastal areas of the city that require special attention. This inequality is often not realized so there is a continuous gap. Therefore, the purpose of holding the work program for the distribution of 1,800 iftar packages is to raise the profile of areas that can be categorized as leading, remote, and underdeveloped areas or what we call 3T areas, especially those in the city of Tasikmalaya. Apart from that, the purpose of holding this community service program is to be a solution to the problems of people living in the coastal areas of Tasikmalaya city who are less able to meet their food needs when breaking their fast. The scope of targets in this work program is children with disabilities, accident victims, orphans, the elderly, and people who have trauma. In carrying out this community service program, the method used is by using a participatory approach, meaning that the implementation of the work program this time involves directly with certain stakeholders, both partners, and donors in the direct distribution of the Iftar package to the seventeen predetermined target areas. The results achieved from this community service program are that the people who are the targets feel very helpful in meeting their food needs when breaking their fast, as well as for the social community it is useful in recording community records to follow up or create other work programs that target people with disabilities, accident victims, orphans, elderly, and people who have trauma. This can help those who need special assistance and attention from experts.